2010
DOI: 10.1111/j.1365-2702.2010.03224.x
|View full text |Cite|
|
Sign up to set email alerts
|

The effect of clothes on sphygmomanometric blood pressure measurement in hypertensive patients

Abstract: Sleeves have no effect on blood pressure results. Blood pressure readings taken over the sleeves will be much more practical and time saving in busy departments like emergency rooms, during disasters like earthquake where decisions have to make in minutes. Additionally, it will be time saving for general health screening surveys. Finally, it may have preferable because of hygiene concerns, patient privacy and religious beliefs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 21 publications
2
16
0
Order By: Relevance
“…Our results are in line with data in six previous studies [1,[5][6][7][8][9] as shown in Table 4. As there were slight differences in the protocols used in these studies, we present the relevant differences for comparison in Table 4.…”
Section: Discussionsupporting
confidence: 96%
See 1 more Smart Citation
“…Our results are in line with data in six previous studies [1,[5][6][7][8][9] as shown in Table 4. As there were slight differences in the protocols used in these studies, we present the relevant differences for comparison in Table 4.…”
Section: Discussionsupporting
confidence: 96%
“…In clinical practice, these recommendations on removal of clothing are often not followed, and for practical or comfort reasons, clothing is left underneath the cuff. There are some studies that support this practice [1,[5][6][7][8][9], but these have some flaws. Previous studies had the limitations of very few BP readings, use of only one standard cuff bladder size, and absence of randomization.…”
Section: Introductionmentioning
confidence: 97%
“…The mean variables were as follows: age, 45.5 years; BMI, 23.4; and clothing thickness (of 77.1% of patients), < 1 mm. Pinar et al11 studied 258 male/female hypertensive patients (clothing thickness, ≤ 2 mm; BMI range, 20–41) with a mercury-filled column sphygmomanometer. SBP and DBP were measured over a sleeve and on a bare arm.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these studies included normotensive and hypertensive patients; featured wide age, body mass index (BMI), and clothing thickness ranges; and used automatic sphygmomanometers 7-10. In only one study, a mercury-filled column sphygmomanometer was used for the blood pressure measurements 11. The studies also used various measurement numbers and positions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation